2017
DOI: 10.1016/j.gr.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Yarlung suture mélange, Lopu Range, southern Tibet: Provenance of sandstone blocks and transition from oceanic subduction to continental collision

Abstract: With the aim of better understanding the history of ocean closure and suturing between India and Asia, we conducted a geologic investigation of a siliciclastic matrix tectonic mélange within the western Yarlung suture zone of southern Tibet (Lopu Range region, ~50 km northwest of Saga). The siliciclastic matrix mélange includes abundant blocks of ocean plate stratigraphy and sparse blocks of sandstone. Metapelite and metabasite blocks in the mélange exhibit lower greenschist facies mineral assemblages, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 109 publications
(273 reference statements)
0
25
0
Order By: Relevance
“…In alternative, a trench-slope-basin setting may be envisaged for the Luogangcuo Formation. Previous studies, however, have suggested that the Transhimalayan subduction complex was rather small without large ridges or thrust slices before the onset of the initial India-Asia collision (An et al, 2017;Metcalf and Kapp, 2017), and therefore insufficiently wide and prominent to host a trench-slope basin on top. Most important, the Luogangcuo Formation lies in fault contact with the Xiukang Mélange.…”
Section: Depositional Settingmentioning
confidence: 92%
See 2 more Smart Citations
“…In alternative, a trench-slope-basin setting may be envisaged for the Luogangcuo Formation. Previous studies, however, have suggested that the Transhimalayan subduction complex was rather small without large ridges or thrust slices before the onset of the initial India-Asia collision (An et al, 2017;Metcalf and Kapp, 2017), and therefore insufficiently wide and prominent to host a trench-slope basin on top. Most important, the Luogangcuo Formation lies in fault contact with the Xiukang Mélange.…”
Section: Depositional Settingmentioning
confidence: 92%
“…In the Xigaze forearc basin, the middle-lower Ngamring Formation contains detrital zircons with typical Gangdese arc signatures (Mesozoic ages and positive εHf(t) values), whereas the upper Ngamring and Padana formations yield numerous zircon grains with either pre-Mesozoic or Mesozoic ages and positive or negative εHf(t) values, testifying to provenance from both Gangdese arc and central Lhasa terrane (Wu et al, 2010;An et al, 2014;Orme et al, 2015;Orme and Laskowski, 2016). Adjacent to the Luogangcuo Formation, the Xiukang Mélange contains numerous blocks of: (i) Upper Cretaceous to Eocene lithic-rich volcaniclastic sandstones derived from the Gangdese arc and central Lhasa terrane, (ii) pre-Cretaceous quartzose sandstones derived from the Indian subcontinent; and, (iii) Middle Triassic to Lower Cretaceous chert or Middle Permian to Upper Cretaceous limestone derived either from the distal Indian margin or the Neo-Tethyan oceanic domain (Shen et al, 2003a(Shen et al, , 2003bCai et al, 2012;An et al, 2017;Metcalf and Kapp, 2017).…”
Section: Provenance Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter two formations are considered as the syncollisional sedimentary records (e.g., Ding et al, 2005; Hu, Wang et al, 2016; Jia et al, 2005; Orme et al, 2015; Wan et al, 2001). The sandy‐muddy mélange subzone of the YZSZ outcrops east to Zedong and contains abundant syncollisional sedimentary records (e.g., An et al, 2017; Burg & Chen, 1984; Ding et al, 2005; Metcalf & Kapp, 2017, 2019). Within the subzone, the syncollisional sediments are characterized by the Paleocene radiolarian cherts and sandstones in Saga area (e.g., DeCelles et al, 2014; Ding et al, 2005; Hu et al, 2015) and by the Zongzhuo mélange dominated by olistoliths in Gyangze area (e.g., Cai et al, 2011; Li et al, 2005; Wu et al, 1977; Wu et al, 2014).…”
Section: Geological Settingmentioning
confidence: 99%
“…Indeed, sedimentary records have been widely used to study the collisional process in the western and central YZSZ (Figure 1). Up to date, the initial collision age has been precisely, to some degree, constrained to ~56–60 Ma in the western (Critelli & Garzanti, 1994; Gaetani & Garzanti, 1991; Garzanti et al, 1987; Najman et al, 2017) and central YZSZ (e.g., DeCelles et al, 2014; Hu et al, 2015; Hu, Wang et al, 2016; Metcalf & Kapp, 2017; Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%